Resistance to preservatives and the viable but non-culturable state formation of Asaia lannensis in flavored syrups - Wen, Xia; Chen, Yiwen; Zhang, Shuyao; Su, Ai-ting; Huang, Di; Zhou, Gang; Xie, Xiaobao; Wang, Jufang (Frontiers in Microbiology, 2024)
Food security is a crucial issue that has caused extensive concern, and the use of food flavors has become prevalent over time. This study aimed to examine the bacterial contamination of flavored syrup through molecular biological techniques, preservative susceptibility testing, viable but nonculturable (VBNC) state induction testing, and a transcriptome analysis to identify the causes and develop effective control measures. The molecular biological identification revealed that Asaia lannaensis WLS1-1 is a microorganism that can spoil food and is a member of the acetic acid bacteria families. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests showed that WLS1-1 was susceptible to potassium sorbate (PS), sodium benzoate (SB), and sodium sulfite (SS) at pH 4.0. It revealed a progressive increase in resistance to these preservatives at increasing pH values. WLS1-1 was resistant to PS, SB and SS with an MIC of 4.0, 2.0 and 0.5g/L at pH 5.0, respectively. The MIC values exceed the maximum permissible concentrations that can be added. The induction test of the VBNC state demonstrated that WLS1-1 lost its ability to grow after 321 days of PS induction, 229 days of SB induction and 52 days of SS induction combined with low temperature at 4ºC. Additionally, laser confocal microscopy and a propidium monoazide-quantitative polymerase chain reaction (PMA-qPCR) assay showed that WLS1-1 was still alive after VBNC formation. There were 7.192±0.081 (PS), 5.416±0.149 (SB) and 2.837±0.134 (SS) log10(CFU/mL) of viable bacteria. An analysis of the transcriptome data suggests that Asaia lannaensis can enter the VBNC state by regulating oxidative stress and decreasing protein synthesis and metabolic activity in response to low temperature and preservatives. The relative resistance of Asaia lannaensis to preservatives and the induction of the VBNC state by preservatives are the primary factors that contribute to the contamination of flavored syrup by this bacterium. To our knowledge, this study represents the first evidence of the ability of Asaia lannaensis to enter the 3 VBNC state and provides a theoretical foundation for the control of organisms with similar types of activity.